Oxide Nanomaterials Based on SnO2 for Semiconductor Hydrogen Sensors - George Fedorenko; Ludmila Oleksenko; Nelly Maksymovych (Advances in Materials Science and Engineering)
Nanosized tin dioxide with an average particle size of 5.3 nm was synthesized by a sol-gel method and characterized by IR spectroscopy, TEM, X-ray, and electron diffraction. The obtained SnO2 can be used as initial material for creation of gas-sensitive layers of adsorption semiconductor sensors. Addition of palladium into the initial nanomaterial allows to improve response to hydrogen of such sensors in comparison with sensors based on undoped SnO2 and provides fast response and recovery time, a wide measuring range of hydrogen content in air ambient, and good repeatability of the sensor signal. Such promising properties could make useful the sensors based on these nanomaterials for devices intended to determine hydrogen in air.